(3GdCMcGe GdTQYjI GdcHQi ef MOjK QShd Gddg Udi Gddg Ydjg hSdes - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH ef CQOc QcYI ef GdaLQ s
(3BNQgG (B:s
(3hjfJgi HHGH eG LGA ai GdeGd ef GdMbhb Shi GdRcGI s
(3GdfSNI HgG MhGTs
(3Ydjg Jedc eDQN HSfI (B852(3g` hJhbjY dGHf MLQ GdYSbdGfi Ydi GdETgGO Hhba GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
Keywords: (3GdMOjK h GdeUWdMs